Virtual laboratory of Andaliman tissue culture integrated with islamic values - Adi Hartono; Indayana Febriani Tanjung; Irwan Syahputra (Universitas Negeri Jakarta, 2021)
Nowadays, the world is being hit by a Corona virus outbreak which has an impact on every line of life including the field of Education which encourages students to take online learning. This study aims to develop a Virtual Laboratory of Andaliman Network Culture integrated with Islamic values as an interactive learning media to overcome problem obstructions in practicum activities as well as to strengthen the internalization of Islamic values and insights into the local potential of students in The State Senior High School 11 Medan, North Sumatera, Indonesia. This research was conducted using Research and Development (R & D) with the ADDIE approach (Analysis, Design, Development, Implementation, Evaluation). The results showed that the percentage of media validity by Material Expert validators was 98.61%, Islamic Values Material Expert validators were 90.62%, Virtual Laboratory Expert validators were 93.96%, and Field Practitioner Expert validators (Biology Teachers) were 93.75% with the category of evaluation of all validators as very good. Meanwhile, the percentage of student responses to the media reached 63.88% in the good category. Thus, it is highly recommended to use the Virtual Laboratory which was developed because it has tested validly to increase understanding about mechanism Plant Tissue Culture with Islamic Values and Local Potential.